Pendidikan Kesehatan Dengan Pendekatan Health Belief Model Meningkatkan Perilaku Perempuan Menopause Tentang Resiko Osteoporosis - Yhenti Widjayanti (Jurnal Keperawatan Muhammadiyah, 2022)
Objective:   Menopausal women are at high risk for osteoporosis. Osteoporosis can be prevented by health behavior. Prevention efforts are strongly influenced by the results of a person's health beliefs.  Purpose of this study was to   analyze the influence of health education with a health belief model approach on the behavior of menopausal women on the risk of osteoporosis . Methods:  Design of this study  was a pre-experimental pre-posttest design. The research subjects were 44 postmenopausal women who met the inclusion criteria. This study used a simple random sampling technique. This study’s variables were health education,  knowledge, attitudes and actions of menopausal women on the risk of osteoporosis during menopause. Data collected by questionnaire and  be analyzed descriptively by the percentage and statistical test and  Wilcoxon signed rank test. Results: The results showed that before intervention was given 43.2% respondents had fair level of knowledge,29.5%  respondents had  poor and 27.3%, respondents had good knowledge,  56.8% respondents had negative attitude and 43.2% had  positive attitude. While adequate action 45.5 % had less,  31.8% had enough and 22.7% respondents had adequate action.  After getting the intervention with a good knowledge level of 61.4%, 34.1% fair and 4.5% poor, while positive attitudes were 84.1% and negative attitudes were 15.9%, for good actions 61.4%, enough 25.0 % and less actions 13.6%. The results of statistical tests using the Wilcoxon signed rank test obtained each p <α , α= 0.5, which means that there was an effect of health education with the health belief model approach with the behavior of menopausal women on the risk of osteoporosisConclusion:  Health education with a health belief model approach effective to increase  knowledge of menopausal women so that they can form a positive attitude so that they motivate them to do menopause prevention actions.